(3QSGdI dHGH GdJYQjV aj PcQ GdCjGe GdHjVs - (3CHh YHO Gddg eMeO Hf GdHGYhfjs ((3eMeO Hf Rjf GdOjf gdGd s)
(3ChdgG (B:s
(3jbHd GdCQV hjfei ef OYGeg eG jMGaX Ydjg ai bQHg hHYOg hjdGRe ajg WQb GdENdGU s
(3BNQgG (B:s
(3djS GdTJGA ef GdLdjO LdhOkG aGdHS abO HQO GdReGf HQhOkG hGf jJbHd efG hjJLGhR YfG Bejf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B10s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3HghGeTgG JUMjMGJ JUhas
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3eLGejY JjehQ (B266) s
Keywords: (3GdeLGejYs